Avaliação e proposição de critérios de outorga para lançamento de efluentes em corpos d'água - Marilia Carvalho de Melo (2006)
The purpose of this work was to evaluate the Mixing Equation and the Streeter-Phelps model as tools for the definition of entitlement criteria. These models are normally used for the quantitative appraisal of the effect of a discharge into a water body. Model evaluation was performed by testing its influencing factors. This work was divided in two parts. In thefirst part, 12 scenarios were simulated in a hypothetic basin, in which the reference flow and BOD content, previous to the assigned discharges, were made to vary. In this first part it was also tested: (i) the influence of user location on the value of the minimum dilution flow to configure acceptable discharge conditions; (ii) model behaviour under realconditions of two regions of the State of Minas Gerais, Brazil: one with deficiency and the other with abundance of water; and (iii) the impact on the basin of limit-condition discharges and of discharges just to keep standard water body BOD values, as defined by the Brazilian environmental legislation. In the second part, the same scenarios were applied to a real basin, that is, the Ribeirão Marmelada Basin, situated in the municipalities of Abaeté, Cedro do Abaeté and Quartel Geral, in the State of Minas Gerais, Brazil. Results have shown that both models can be used for the definition of discharge entitlement criteria. However, Streeter-Phelps model may be considered as the one which betterrepresents real discharge conditions because it takes into consideration the self-purification capacity of the water body. It was also possible to conclude that previous discharges must be considered in the calculation of the minimum dilution flow rate for an entitlement. Finally, it is recommended that the choice of the reference flow rate and its availableportion be preceded by a careful analysis of the climatic and geo-morphological conditions.